Beco de vó Dola: territorialidade e ancestralidade negra em Vitória da Conquista - Passos, Flávio José dos (2012)
Upon searching to interpret Dola s Alley as a "web of meanings", entangled in the house and in the shed and in the alley itself, where the identitary subjects, with whom this anthropological work dialogues, are defined, our primary aim is to understand the family, culture and group dynamics of this group of blood and of saint. This search means a step by step examination into the process of the formation of the family group from Vó Dola s ancestral memory, from the social and genealogical memory that is present in the formation, occupation and assertion of Bairro das Pedrinhas and the relationship between this memory/collective identity and the shed of candomblé angola. In this way, from the narratives by the alley s women, as well as the testimonies by their sons and daughters, grandchildren, stepchildren and neighbors, one scrutinizes the feeling of ethnic-racial belonging within Vó Zita, Mãe Fátima, Madrinha Elza and Vó Dola s community-family, as "Great Mothers" of an extended family and a community of Indigenous-African religious tradition. Thus, upon understanding the Bairro da Rua das Pedrinhas, but mainly Dola s Alley in the present work, as the black territory par excellence, we contribute to a greater visibility of the African-Indigenous history and culture in the urban and territorial dynamics in Vitória da Conquista and its region